Dissecting susceptibility from exogenous triggers: the model of alopecia areata and associated inflammatory skin diseases. (28th September 2015) - Garzorz, N.; Alsisi, M.; Todorova, A.; Atenhan, A.; Thomas, J.; Lauffer, F.; Ring, J.; Schmidt‐Weber, C.; Biedermann, T.; Eyerich, S.; Eyerich, K.
Abstract: Background: Alopecia areata (AA) is a T‐cell‐driven autoimmune disease of the hair follicle and frequently reported to be associated with inflammatory skin diseases (ISD) such as atopic eczema (AE) or psoriasis. Interestingly, AA on the one hand and both AE and psoriasis on the other hand are believed to be driven by mutually antagonistic T‐cell subsets. Objective: To characterize AA‐specific T‐cell profiles and inflammatory pattern by intra‐individual comparison of AA and coexistent ISD. Methods: 112 patients with AA were recruited and investigated for coexisting ISD. In‐depth analyses were performed in patients with AA and AE ( n = 2), AA and psoriasis ( n = 1), AA and psoriasis and AE ( n = 1) and AA and lichen planus ( n = 1), using histology, immunohistochemistry and cytokine staining of T cells isolated from lesional skin. Results: Of 112 AA patients investigated, 23 suffered from an ISD. The prevalence of AE, vitiligo, psoriasis and lichen planus was higher in the investigated AA cohort than in the normal population. The clinical as well as histological phenotype of AA the coexistent ISD were unequivocal. In line with this, T‐cell infiltrates were found to be disease‐characteristics with AA and lichen planus dominated by CD8+ and IFN‐γ+ TNF‐α+ producing T cells while psoriasis lesions in the same patients were dominated by IL‐17+ and AE by IL‐4+ T cells. Conclusion: AA patients have a higher incidence of various T‐cell‐driven inflammatory skin diseases than the normal population, a phenomenon which might relate to over‐activation of skin‐homing T cells and to specific immune triggers as the primary cause of inflammation. More importantly, we showed that by using AA as a model disease, our approach of intra‐individual comparison of distinct inflammatory responses in the same patient is feasible and offers the unique possibility to gain insights into disease pathogenesis independent from genetic susceptibilities.